Increasing Speaking Using Song Twinkle Twinkle Little Star for Beginner - Ni Ketut Suciarti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study investigates the effectiveness of using the nursery rhyme "Twinkle Twinkle Little Star" to enhance English speaking skills for beginner learners. Through a qualitative classroom-based approach, the research examines how the song's repetitive structure, simple vocabulary, and melodic patterns aid in improving pronunciation, fluency, and confidence in speaking. The methodology involves structured singing activities, pronunciation drills, and creative adaptations to transition from melodic repetition to spontaneous speech. Findings indicate significant improvements in phonological awareness, particularly with challenging sounds, as well as increased student engagement and reduced speaking anxiety. However, the study also reveals that while musical elements effectively build prosodic skills, supplementary exercises are necessary to develop grammatical accuracy and unassisted conversation abilities. The results suggest that traditional nursery rhymes, when combined with targeted speaking strategies, can serve as a valuable foundation for beginner language acquisition. This research contributes to pedagogical approaches in TESOL, highlighting the benefits and limitations of song-based instruction for developing oral proficiency in young learners.